Influence of Low-Frequency Sonolysis on the Kinetics of Liquid-Phase Chemical Reactions Involving Associates - Kulagina, Tatiana P.; Smirnov, Lev P.; Andrianova, Zoya S. (Journal of Applied Solution Chemistry and Modeling, 2018)
The influence of low-frequency sonolysis on the kinetics of liquid-phase bimolecular liquid-phase reactions was studied by mathematical modeling with due regard for the association of starting reagents into dimers and trimers. With increasing frequency and amplitude of low-frequency sonic waves (up to some critical value), we observed the disappearance of trimers and concomitant cessation of the reaction. This observation offers an additional tool for controlling reaction rate by the external action of low-frequency vibrations.